Zeolite Membranes for Gas and Liquid Separation: Synthesis and Applications - Qing Wang; Xiaoyu Yang; Bin Wang (Membranes)
The quest for efficient separation technologies is more critical than ever in our rapidly evolving industrial landscape, where the demand for sustainable and cost-effective solutions is paramount [...]